Sagnac Interferometer Based Generation of Controllable Cylindrical Vector Beams - Cristian Acevedo; Angela Guzmán; Yezid Torres Moreno; Aristide Dogariu (International Journal of Optics)
We report on a novel experimental geometry to generate cylindrical vector beams in a very robust manner. Continuous control of beams’ properties is obtained using an optically addressable spatial light modulator incorporated into a Sagnac interferometer. Forked computer-generated holograms allow introducing different topological charges while orthogonally polarized beams within the interferometer permit encoding the spatial distribution of polarization. We also demonstrate the generation of complex waveforms obtained by combining two orthogonal beams having both radial modulations and azimuthal dislocations.